Recommendations for improving the recruiting and hiring of Los Angeles firefighters - Hardison, Chaitra M. (Research report (Rand Corporation), 2015)
In 2014, the City of Los Angeles Mayor's Office sought assistance from the RAND Corporation to find ways to improve the process the city uses to hire firefighters into the Los Angeles Fire Department. RAND conducted a three-month review of Los Angeles's firefighter hiring policies and practices, paying particular attention to their effectiveness and fairness. This report presents the results of that three-month effort. It reviews the city's hiring practices used in the 2013 hiring cycle and in place at the time of the study and outlines a recommended new firefighter hiring process that is intended to increase efficiency of the hiring process, bolster the evidence supporting the validity of it, and make it more transparent and inclusive.